Place to space, space to place: A theoretical discussion on place-making in lost spaces - Yalcin, Deniz; Kurkcuoglu, Eren (Turkish Journal of Sense of Place and Urban Studies, 2023)
In many cities, similar and unidentified public space applications are carried out without considering user's preferences and behaviors ending up with lack of functionality and non-site-specific designs. Healthier and functional spaces can be achieved by increasing the interaction of users with their both structural and social environment. This article focuses on what causes an area to turn into an unused one, which tools can be applied to design or redesign it, and how effective they were. In this manner, lost space is examined to define the problem and placemaking in urban settings is explored to find the solution conceptually. Lost spaces refer to areas that are unattractive and not useful to the surrounding environment or people and require a redesign or renovation. Placemaking is the process of reshaping a space to make it more attractive and useful and to create a sense of place. The linkage between them is apparent as placemaking acts like a cure for lost spaces.  Examples of placemaking projects which are Zümrütevler, Bright Stripes Installation and Campus Martius are evaluated with the key attributes defined by Project for Public Spaces. Intangibles of each attribute are considered for each project in terms of their presence. They are successful examples of how placemaking can be used to engage the community in the design process and create more livable urban spaces. But, Campus Martius stands out because of its’ placemaking types. As a result of the research, it’s understood that actions to revitalize a lost space should be user centered and be also more effective with data collection and design process improvements.